(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
The rehabilitation of amputated clients seeks to reintegrate them into society, allowing them to resume daily and professional activities, improving their quality of life. The objective is to report two support cognitive-behavioral therapy groups with amputated clients conducted by psychology trainees under supervision, accompanied by the multidisciplinary rehabilitation team and receiving the prosthesis in a rehabilitation center of a private college. Group 1: 12 clients (7 men, 5 women), mean age 54 years (SD = 8). Group 2: 8 clients (5 men, 3 women), mean age was 44 years (SD = 15). 16 meetings were held with each group weekly. Topics covered: phantom pain, self-image, training in problem solving, receiving the prosthesis, social support, identifying and evaluating automatic thoughts that interfered negatively with treatment adherence, self-efficacy and coping card. Clients were more participative in the activities, more involved in the sessions and homework, more aware of the difficulties and more proactive in the prosthesis placement